G152(P) A quality improvement project for management of well babies with jaundice in a district general hospital. (25th October 2020) - Coburn, J; Martin, J; Chavan, A; English, S; Hickey, A; Gandhi, R
Abstract : Background: An audit performed on the management pathway of well babies with jaundice referred from community demonstrated long waiting times in A&E and on the local SCBU, with pathways of care not clarified. This posed an increased risk for babies being exposed to infection in A&E and increased pressure on nursing and medical staff. In view of this, a new midwifery led pathway was implemented in May 2019. This has clear guidelines and SOP for referrals and exclusions by the community team and escalation pathways to medical staff. Well babies are assessed in a walk in clinic by midwives using transcutaneous bilirubinometers (TCB) in the maternity assessment unit (MAU). Further referral to paediatric staff are made if they fulfil specific high risk criteria or bilirubinometer reading is >250umol/l. Unwell babies are referred directly to A&E for further assessment and management. Objective: To determine the safety and effectiveness of midwifery led pathway To determine reduction in the waiting times To determine cost implications of this service Method: Prospective data was collected for all babies being referred and assessed following the service change. Waiting times and cost effectiveness were analysed and compared to previous pathway. Results: The number of babies per month being assessed by the midwifery team has remained same as that seen previously (Average 72babies/month). Average age at referral, gestational age and birth weight were similar in both pathways: 3.9 days, 39 weeks GA and 3377gm respectively. Waiting times reduced significantly from average of 120 minutes to 31 minutes with the new pathway. Only 15% of the babies assessed in MAU were referred for further assessment to medical team. The one-time cost of purchasing of TCB was £3400 as compared to cost of blood tests performed in one month was £1499.94. Conclusion: Midwifery led pathway significantly improved waiting times for babies to be assessed, mitigating the risks of them being exposed to serious infections in A&E. It is a cost-effective and efficient pathway for assessment of well babies. The pathway provides an adequate safety net for unwell babies as well as babies with risk factors being referred appropriately to the medical team.